Public Service Bureaucracy and the Tradition of Nobility: Cultural Resistance to the New Public Service Ethos - Muhammad Asdar; Andi Asdar; Mashuri Mashuri; Andi Muhammad Yunus; Jumiati Jumiati (Public Resource Innovation Management and Excellence, 2025)
This study analyzes the influence of aristocratic traditions on leadership and public service bureaucratic practices in Bone Regency, South Sulawesi, and examines the forms of cultural resistance that hinder the implementation of the New Public Service (NPS) ethos. Using a qualitative ethnographic approach, data were collected through participant observation, in-depth interviews, and document analysis, then analyzed thematically using a Weberian theoretical framework and the NPS paradigm. The results show that aristocratic traditions are not merely a cultural identity but also a source of political and administrative legitimacy that shapes paternalistic leadership styles and reinforces patron-client patterns within the bureaucracy. In public service practices, formal procedures such as SOPs and digital systems often experience decoupling from informal mechanisms that still emphasize personal closeness and status symbols. This cultural resistance creates a paradox: the bureaucracy appears institutionally modern, but its practices remain patrimonial. This study emphasizes that bureaucratic reform in regions with a noble heritage must consider the local cultural context, by reinterpreting aristocratic values as social capital to support participatory, inclusive, and egalitarian public services. These findings provide theoretical contributions to contextual public administration studies as well as practical implications for bureaucratic reform strategies in similar areas.